More Policies, More Work? An Epidemiological Assessment of Accumulating Implementation Stress in the Context of German Pension Policy - Christian Adam (Regulation & Governance, 2024)
Research on policy accumulation established the hypothesis about a creeping divergence between implementation burdens and implementation capacity. This paper revisits this hypothesis using improved measures of implementation burden. Using official data on administration and enforcement costs, it finds that policy accumulation does raise implementation stress within the German Statutory Pension Insurance, analyzed as a least-likely case to do so. This finding supports the “implementation-gap hypothesis.” More generally, however, the paper serves as a “prove of concept” of how to adopt an epidemiological perspective within implementation research. This perspective is characterized by systematically capturing the changing prevalence of implementation stress within administrative organizations. It enables future research on how to deal with policy growth more effectively by raising awareness for whether and where implementation burden and capacity diverges strongly, and by helping to identify “best practice” cases able to cope with this divergence successfully.
Keywords: 330